2006
DOI: 10.1002/elps.200500460
|View full text |Cite
|
Sign up to set email alerts
|

Study of binding stoichiometries of the human immunodeficiency virus type 1 reverse transcriptase by capillary electrophoresis and laser‐induced fluorescence polarization using aptamers as probes

Abstract: Binding stoichiometries between four DNA aptamers (RT12, RT26, RTlt49, and ODN93) and the reverse transcriptase (RT) of the type 1 human immunodeficiency virus (HIV-1) were studied using affinity CE (ACE) coupled with LIF polarization and fluorescence polarization (FP). The ACE/LIF study showed evidence of two binding stoichiometries between the HIV-1 RT protein and aptamers RT12, RT26, and ODN93, suggesting that these aptamers can bind to both the p66 and p51 subunits of the HIV-1 RT. Only one binding stoichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…CE analysis of each sample was repeated three times. The fluorescence polarization (FP) values were calculated from the obtained intensity of the horizontally polarized fluorescence (I h ) and vertically polarized fluorescence (I v ) according to the following equation [34]:…”
Section: Ce/lifp Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…CE analysis of each sample was repeated three times. The fluorescence polarization (FP) values were calculated from the obtained intensity of the horizontally polarized fluorescence (I h ) and vertically polarized fluorescence (I v ) according to the following equation [34]:…”
Section: Ce/lifp Analysismentioning
confidence: 99%
“…It is also possible to differentiate the protein-DNA complexes with different binding stoichiometry by fluorescence polarization. Previous study demonstrated that the two complexes of human immunodeficiency virus type 1(HIV-1) reverse transcriptase (RT) and RT 26 aptamer with stoichiometry of 1:1 and 1:2 showed significantly different fluorescence polarization value (P = 0.098 for 1:1, and P = 0.039 for 1:2) [34]. In our case, since only one complex peak was observed, the complexes of thrombin-aptamer with different binding stoichiometries should be overlapped if they are to formed, and the fluorescence polarization of the complex peak should change with the varied concentration of thrombin.…”
Section: Complex Formation and Ce Separationmentioning
confidence: 99%
“…In addition, using LIF polarization detection in pre-eq CZE studies it is possible to identify complex formation even in the absence of separation between the free fluorescent molecule and the complex [160]. In a recent study, the polarization detection was useful for identification of the stoichiometries of the formed complexes [142]. The sensitivity of LIF polarization was reported to be of the same magnitude as LIF detection [160].…”
Section: Methodological Developmentsmentioning
confidence: 94%
“…Upon excitation with plane-polarized light the emitted fluorescence of a fluorescently labeled compound becomes depolarized due to the rotation of the molecule during excitation. Binding to another molecule, e.g., a protein will lower the extent of depolarization because the larger complex will rotate more slowly and the emitted light will be more polarized leading to higher polarization values [142,159]. Thus, the peaks related to the unbound fluorescent probe and the complex will have different polarization allowing identification of the complex.…”
Section: Methodological Developmentsmentioning
confidence: 95%
See 1 more Smart Citation